The stalked filter feeder Siphusauctum lloydguntheri n. sp. from the middle Cambrian (Series 3, Stage 5) Spence Shale of Utah: its biological affinities and taphonomy. (7th August 2017) - Kimmig, Julien; Strotz, Luke C.; Lieberman, Bruce S.
Abstract: We describe a new species of enigmatic stalked filter feeder, Siphusauctum lloydguntheri, from the middle Cambrian (Series 3, Stage 5) Antimony Canyon locality of the Spence Shale of northern Utah. The described specimen is the only one known from the Spence Shale, represents the first occurrence of Siphusauctum outside the Burgess Shale, and is only the second described species from the genus. Siphusauctum lloydguntheri n. sp. differs from S . gregarium O'Brien and Caron, 2012 in the shape of its calyx and the position of the digestive tract. The new species provides some additional information about the possible affinities of enigmatic stalked Cambrian filter feeders, as well as the taphonomic pathways that lead to preservation of Siphusauctum .